2003
DOI: 10.1037/0735-7036.117.4.440
|View full text |Cite
|
Sign up to set email alerts
|

Use of Position and Feature Cues in Discrimination Learning by the Whiptail Lizard (Cnemidophorus inornatus).

Abstract: Animals use a variety of cue types to locate and discriminate objects. The ease with which particular cue types are learned varies across species and context. An enormous literature contains comparisons of spatial cue use to use of other cue types, but few experiments examine the ease with which various nonspatial cues are learned. In addition, few studies have examined cue use in reptiles. Thus, the authors compared whiptail lizards' (Cnemidophorus inornatus) ability to learn and reverse a discrimination usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 58 publications
3
33
0
1
Order By: Relevance
“…The greater accuracy exhibited by all three species on this spatial task, in contrast to the color task, suggests either that spatial reversal is inherently a less difficult problem or that there were significant carryover effects of the birds' prior training on color stimuli. Spatial position has been found to be less difficult to reverse than color or shape in some taxa (reviewed in Day, Ismail, & Wilczynski, 2003) but more difficult in others (e.g., Doty & Combs, 1969). Transfer between two series of reversals when the discriminated dimensions are changed (i.e., between color and position or between color and orientation) has been found to be negative or negligible in studies on both pigeons and rats (Durlach & Mackintosh, 1986;Mackintosh & Holgate, 1969;Mackintosh, McGonigle, Holgate, & Vanderver, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…The greater accuracy exhibited by all three species on this spatial task, in contrast to the color task, suggests either that spatial reversal is inherently a less difficult problem or that there were significant carryover effects of the birds' prior training on color stimuli. Spatial position has been found to be less difficult to reverse than color or shape in some taxa (reviewed in Day, Ismail, & Wilczynski, 2003) but more difficult in others (e.g., Doty & Combs, 1969). Transfer between two series of reversals when the discriminated dimensions are changed (i.e., between color and position or between color and orientation) has been found to be negative or negligible in studies on both pigeons and rats (Durlach & Mackintosh, 1986;Mackintosh & Holgate, 1969;Mackintosh, McGonigle, Holgate, & Vanderver, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Two individuals were able to reverse their association, while two individuals continued to remove the previously rewarded stimulus and never manipulated the new target (table 1). Studies of reptilian cognition are extremely limited; however, evidence suggests that spatial reversal is an easier cognitive task than reversal based on visual feature cues (reviewed in Day et al [12]). In our reversal task, the degree of similarity between the cues was higher than that previously used in reptiles (reviewed in Day et al [12]), suggesting that reptiles might be more efficient than previously reported at discriminating the features of visual stimuli (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In studies in which multiple cognitive tasks have been used, results indicate that the ability of an individual to solve one cognitive task is not a predictor of success across multiple cognitive tasks [9,10]. Thus, a robust demonstration of behavioural flexibility should show that individuals are capable of solving multiple cognitive tasks, an approach that is not commonly used, especially in ectothermic vertebrates (see [11,12] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…location of predators in their surroundings or obstacles to refuges). Although the available evidence shows that snakes and lizards are capable of learning the spatial location of food items or shelters in the laboratory [4,[7][8][9][10][11], some studies seem to suggest that they have limited spatial cognitive abilities and require many training trials to learn simple spatial tasks [4]. Here, we used an ecologically relevant anti-predator context to study whether lizards show evidence of flexible spatial learning using two replicate groups of lizards maintained in large semi-natural outdoor enclosures.…”
Section: Introductionmentioning
confidence: 99%